Inflammation and disease: Modelling and modulation of the inflammatory response to alleviate critical illness. Issue 12 (December 2018) - Day, Judy D.; Cockrell, Chase; Namas, Rami; Zamora, Ruben; An, Gary; Vodovotz, Yoram
Abstract: Critical illness, a constellation of interrelated inflammatory and physiological derangements occurring subsequent to severe infection or injury, affects a large number of individuals in both developed and developing countries. The prototypical complex system embodied in critical illness has largely defied therapy beyond supportive care. We have focused on the utility of data-driven and mechanistic computational modelling to help address the complexity of critical illness and provide pathways towards discovering potential therapeutic options and combinations. Herein, we review recent progress in this field, with a focus on both animal and computational models of critical illness. We suggest that therapy for critical illness can be posed as a model-based dynamic control problem, and discuss novel theoretical and experimental approaches involving biohybrid devices aimed at reprogramming inflammation dynamically. Together, these advances offer the potential for Model-based Precision Medicine for critical illness. Highlights: Acute inflammation is a highly dynamic response to infection or injury. The complexity of acute inflammation hinders therapy discovery for sepsis, traumatic injury, and critical illness. Dynamic data-driven and mechanistic modeling approaches can elucidate changes in complex inflammatory signalling networks. Mechanistic model-based control approaches and advanced computational methods may provide strategies for precision medicine. A novel class of engineered biohybrid devices may allow for personalized, fine-grained dynamic control of acute inflammation.